단독 하사근염으로 발현한 특발안와염 1예 - 김기현(Gee-Hyun Kim); 박미라(Mi-Ra Park) (Daihan angwa haghoi jabji, 2021)
목적: 하사근에 단독으로 발현한 특발안와염 증례를 국내 최초로 보고한다. 증례요약: 54세 남자 환자가 2개월 된 좌안 하안검 부종, 좌안 상내전, 하내전 시 통증, 양안 수직복시를 주소로 내원하였다. 환자는 머리를 우측으로 5° 가량 기울인 모습을 보였고, 좌안 결막충혈, 눈꺼풀 틈새의 상대적인 좁아짐이 관찰되었다. 안구운동검사에서 정면 주시 시 8프리즘디옵터의 좌안 상사시, 4프리즘디옵터의 간헐내사시가 확인되었고, 이는 외전, 하전 및 좌측 머리 기울임 시 악화되었다. 안와 자기공명영상에서 좌안 하사근 비대 소견을 보였으나 전신검사에서 특별한 염증성 질환이 확인되지 않아 좌안 하사근에 발생한 특발안와근염을 추정 진단하였다. 이에 경구 부신피질호르몬을 하루 60 mg 투여, 1개월에 걸쳐 감량하였다. 2개월째 안와 자기공명영상에서 좌안 하사근 비대가 확연히 줄었고, 복시는 소실되었다. 치료 후 7개월째까지 증상 재발 없이 경과 관찰 중이다. 결론: 좌안 하안검 부종 및 양안 수직복시 환자에게 안와 자기공명영상 및 전신검사를 시행하여 좌안 하사근에 발생한 특발안와근염을 진단, 경구 부신피질호르몬으로써 성공적으로 치료하였다. Purpose: To report a case of idiopathic orbital inflammation presenting with isolated myositis of the inferior oblique muscle. Case summary: A 54‐year‐old man presented with swelling on the left lower lid, pain on superonasal and inferonasal gaze, and binocular diplopia for 2 months. His head was tilted to the right by about 5° and mild conjunctival injection and 3 mm narrowing of palpebral fissure of the left eye compared to the other eye were observed. Eight prism diopter (PD) left hypertropia and 4 PD intermittent esotropia were noted on primary gaze, which worsened on leftward gaze, downward gaze, and left head tilt. Orbital magnetic resonance imaging (MRI) showed enhanced hypertrophy of the left inferior oblique muscle. Systemic work‐up for possible inflammatory diseases yielded negative results. Therefore, a presumptive diagnosis of idiopathic isolated myositis of the left inferior oblique muscle was made. The patient was treated with 60 mg of oral corticosteroid per day for the first week, and the dose was tapered for 1 month as the symptoms reduced. Two months later, the patient became free from any symptoms and follow- up orbital MRI showed a significant decrease in size of the left inferior oblique muscle. There have been no signs of recurrence for 7 months. Conclusions: A presumptive diagnosis of idiopathic isolated myositis of the inferior oblique muscle was made in a patient with swelling of the left lower lid and binocular diplopia based on orbital MRI and systemic work‐up. Good results were achieved with oral corticosteroid therapy. KCI Citation Count: 0